Hungary on the way between East and West or the civilisation adventure of the early medieval Magyars - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2025)
The memory of the earliest relationships between the Hungarians, who emigrated to the Carpathian Basin, and the local population was reflected in the later tradition noted by the Hungarian chroniclers. The people named Sclavi had their own tradition, which was also used by the Gesta Hungarorum of the anonymous notary of King Béla (III) in the story of the pastores Romanorum and of the Romans escaping to Germany. The story of Svatopluk written by Simon of Kéza and the episode of the marriage of Menumorout's daughter with the Hungarian dauphine Zolta in the notary's Gesta Hungarorum also had local roots. In these stories, one might notice traces of the Great-Moravian tradition, which is present through its political aspect connected to the person of Svatopluk. The other aspect of this tradition, namely its cultural and religious dimensions, which are illustrated by the deeds of St Cyril and Methodius, was not important for the Hungarians, therefore it found no place in the narratives from this country. However, the newcomers met both main branches of the Christianity, i.e. eastern (or Greek and maybe Slavic) and western (Latin) variations, in their new fatherland/homeland. The first decades of the Hungarian's presence in the Carpathian Basin were a period of domination of the eastern model of Christianity among them, nevertheless after the defeat of the Hungarians at the Lechfeld, the Latin missionaries started their activity. St Adalbert, the Bishop of Prague, and his companions were especially active, and they were the real creators of the Hungarian (Latin) Church. However, until the thirteenth century, the Byzantine (Orthodox) Christianity coexisted with the Latin (Roman-Catholic) denomination. Hungary can be therefore considered as a country lying at the borderland between both main cultural spheres of Christian Europe, a situation which is typical for the whole of Central Europe.